Japanese income tourism: The Portuguese luxury hospitality management strategy (before and after Covid-19) - Tavares de Carvalho, P.; Reis, E. (DSOTT'2023, Book of Abstracts, 2023)
This study examines the service quality of luxury hotels operating in Portugal, identifying the factors behind Japanese customers’ satisfaction or dissatisfaction with hotel attributes. The study was based on qualitative and quantitative research methods, taking a four-step approach: first, the relevant literature was reviewed for a better understanding of Japanese culture, Japanese tourists, and the keys to success of Japanese and hotel management; second, content analysis was conducted of Japanese online reviews to compare satisfaction and dissatisfaction with hotel attributes.